Trichoderma strains isolated from Ilex paraguariensis ST. HIL: promising biocontrol agents with chitinolytic activity and plant growth promoter on Lycopersicum esculentum. Issue 1 (1st January 2020) - López, Ana Clara; Alvarenga, Adriana Elizabet; Vereschuk, Manuela Lizz; Barua, Ramona Celeste; Zapata, Pedro Darío; Luna, María Flavia; Villaba, Laura Lidia
Abstract: Ilex paraguariensis Saint Hilaire (St. Hil) is an important crop in the north of Argentina, mainly cultivated in the Misiones province. Trichoderma genera are well known for their biological control and plant growth-promoting properties. The application of Ilex paraguariensis endophytes to improve crop production is an interesting alternative to the use of agrochemicals. To evaluate the capability of Trichoderma spp. endophytes, it was performed antagonism tests of Trichoderma spp. against phytopathogenic fungi associated with these crops using dual culture assay. It was also evaluated the chitinase production of these strains using a colorimetric Somogyi-Nelson method to determine biocontrol capability of these endophytes. Moreover, the capability of plant growth promotion on tomato seeds was evaluated. We observed that Trichoderma was capable to invade and reduce phytopathogen growth and particularly three strains produced chitinase and induced growth promotion on Lycopersicum esculentum seeds.